BUSINESS FEASIBILITY STUDY ON THE DEVELOPMENT OF THE LOCAL FASHION INDUSTRY THROUGH TECHNOLOGY INNOVATION USING KITA LOKAL - Wijaya, Septihani Michella; Yukianti, Chiara Rizka; Johan, Livia; Wijaya, Andi (Graduate Program of Universitas Tarumanagara, 2023)
Kita Lokal is a custom-made clothing service that is equipped with an expedition service, where Kita Lokal uses an application as a consumer intermediary to meet local tailors. Kita Lokal is here as a solution for consumers who want to realize their dream clothes, on the other hand also empowering the talents of local tailors. By using the Business to Consumer model, Kita Lokal presents a fashion quiz containing a number of questions to understand user preferences so that it can be developed in the application, Kita Cart provides history and likes features that can be seen by user followers, Artificial Intelligence (AI) features that can make it easier consumer. Kita Lokal will be the pioneer of applications that provide custom-made and expedition services at the same time as well as presenting an e-commerce platform and fashion community which is realized by increasing support for local fashion, providing outreach services to local fashion producers who do not understand technology, gathering talented local tailors. to change the perception that international brands are better than local brands to be able to compete and even excel in the fashion sector, expand the business market to the national realm, connect consumers with local tailors through the Kita Lokal platform and provide shipping services that make it easier for consumers to receive the results they have received. design with the motto bring life to your design with us.